The development of higher education in Africa : prospects and challenges - Wiseman, Alexander W., 1968-; Wolhuter, C. C. (Charl C.) (International perspectives on education and society, 2013)
This volume of the International Perspectives on Education and Society series investigates the challenges and prospects for higher education in Africa, especially issues of development, expansion, internationalization, equity, and divergence.